Going single but not solo with podocytes: potentials, limitations, and pitfalls of single-cell analysis - Schiffer, Mario (Kidney International, 2017)
Single-cell RNA-sequence (RNA-seq) is a widely used tool to study biological questions in single cells. The discussed study identified 92 genes being predominantly expressed in podocytes based on a 5-fold higher expression compared with endothelial and mesangial cells. In addition to technical pitfalls, the question that is discussed in this commentary is whether results of a single-cell RNAseq study are able to deliver expression data that truly characterize a podocyte.
EVALuna2:34546